2023
DOI: 10.1002/iid3.869
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of nonpharmaceutical analgesia and pharmaceutical analgesia on the labor analgesia effect of parturient women

Abstract: We aimed to compare the labor analgesia effects of nonpharmaceutical analgesia and pharmaceutical analgesia on parturient women.Methods: One hundred and four parturient women with spontaneous births were selected and randomly divided into pharmaceutical and nonpharmaceutical analgesia groups. Before and after analgesia, the Visual Analogue Scale (VAS), parturient satisfaction with analgesia, serum pain stress factors (substance P [SP], neuropeptide Y [NPY], nerve growth factor [NGF], and prostaglandin E2 [PGE2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Initiating NA with lower cervical dilation and prolonged analgesia duration is associated with an increased risk of epidural-related maternal fever [ 5 ]. While pharmaceutical analgesia offers better pain relief and neonatal outcomes than nonpharmaceutical methods, it is associated with longer labor duration and increased postpartum bleeding [ 6 ]. High-quality studies have consistently found no increased risk of intrapartum CD and assisted vaginal delivery with NA, especially when using newer modalities such as low-concentration local anesthetic solutions equivalent to ≤ 0.1% bupivacaine, programmed intermittent epidural bolus, and patient-controlled NA [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initiating NA with lower cervical dilation and prolonged analgesia duration is associated with an increased risk of epidural-related maternal fever [ 5 ]. While pharmaceutical analgesia offers better pain relief and neonatal outcomes than nonpharmaceutical methods, it is associated with longer labor duration and increased postpartum bleeding [ 6 ]. High-quality studies have consistently found no increased risk of intrapartum CD and assisted vaginal delivery with NA, especially when using newer modalities such as low-concentration local anesthetic solutions equivalent to ≤ 0.1% bupivacaine, programmed intermittent epidural bolus, and patient-controlled NA [ 2 ].…”
Section: Introductionmentioning
confidence: 99%